Analisis Halal Value Chain Pada Produk Umkm Studi Kasus Toko Serba Mente (Cemilan & Oleh-Oleh Kolaka) - Ristiyanti Ahmadul Marunta; Akbar M. Sunusi; Amanda Julianti; Nurul Waqia; Eki Pratiwi; Rika Rika (Jurnal Economic Resource, 2026)
This study aims to analyze the implementation of the Halal Value Chain in UMKM Serba Mente, a local snack and souvenir business in Kolaka Regency. The Halal Value Chain emphasizes the application of halal principles throughout all stages of the value chain, including raw material procurement, production processes, packaging, distribution, and marketing. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews with the business owner, direct observation of production activities, and supporting documentation. The findings indicate that UMKM Serba Mente has implemented halal principles consistently across its value chain, although some practices are still conducted in a simple manner. The implementation of the Halal Value Chain contributes positively to product quality, consumer trust, and the competitiveness of UMKM in local and national markets. However, several challenges remain, particularly related to resource limitations and external production factors. This study is expected to provide insights for the development of halal product management among similar UMKM.